Direct growth of thick AlN layers on nanopatterned Si substrates by cantilever epitaxy. Issue 4 (26th September 2016) - Demir, İlkay and Robin, Yoann and McClintock, Ryan and Elagoz, Sezai and Zekentes, Konstantinos and Razeghi, Manijeh
Abstract : AlN layers have been grown on 200 nm period of nanopatterned Si (111) substrates by cantilever epitaxy and compared with AlN layers grown by maskless lateral epitaxial overgrowth (LEO) on micropatterned Si (111) substrates. The material quality of 5–10 µm thick AlN grown by LEO is comparable to that of much thinner layers (2 µm) grown by cantilever epitaxy on the nanopatterned substrates. Indeed, the latter exhibited root mean square (RMS) roughness of 0.65 nm and X‐ray diffraction full width at half‐maximum (FWHM) of 710 arcsec along the (0002) reflection and 930 arcsec along the (10–15) reflection. The corresponding room temperature photoluminescence spectra was dominated by a sharp band edge peak. Back emission ultra violet light emitting diodes (UV LEDs) were fabricated by flip chip bonding to patterned AlN heat sinks followed by complete Si (111) substrate removal demonstrating a peak pulsed power of ∼0.7 mW at 344 nm peak emission wavelength. The demonstrated UV LEDs were fabricated on a cost effective epitaxial structure grown on the nanopatterned Si substrate with a total thickness of 3.3 µm.